Removal of MCPA from aqueous solutions by acid-activated spent bleaching earth - (:unkn) unknown (MARCEL DEKKER INC, 2003)
The removal of MCPA (4-chloro-2-methyl phenoxyacetic acid) from aqueous solutions by activated spent bleaching earth (SBE) was studied as a function of time, initial concentration, adsorbent concentration, and temperature. The Langmuir and Freundlich isotherms were fitted by the adsorption data obtained. The values of Langmuir and Freundlich constants were determined. The adsorption kinetics was described by the Lagergren equation. Mass transfer coefficient and thermodynamic parameters were also calculated. Column experiments were conducted and brekthrough capacities were found for different concentrations and different flow rates. The study demonstrates that acid-treated SBE could be used as an efficient adsorbent for the removal of MCPA-bearing wastewater effluents.
Keywords: MCPA; spent bleaching earth; pesticides; adsorption; adsorption isotherm; LOW-COST ADSORBENT; EQUILIBRIUM UPTAKE; SORPTION DYNAMICS; COLUMN OPERATIONS; ADSORPTION; CARBON; WATER; COPPER; OPTIMIZATION; NICKEL